Cannabis sativa CBD Extract Shows Promising Antibacterial Activity against Salmonella typhimurium and S. newington - Logan Gildea; Joseph Atia Ayariga; Olufemi S. Ajayi; Junhuan Xu; Robert Villafane; Michelle Samuel-Foo (Molecules, 2022)
Products derived from Cannabis sativa L. have gained increased interest and popularity. As these products become common amongst the public, the health and potential therapeutic values associated with hemp have become a premier focus of research. While the psychoactive and medicinal properties of Cannabis products have been extensively highlighted in the literature, the antibacterial properties of cannabidiol (CBD) have not been explored in depth. This research serves to examine the antibacterial potential of CBD against Salmonella newington and S. typhimurium. In this study, we observed bacterial response to CBD exposure through biological assays, bacterial kinetics, and fluorescence microscopy. Additionally, comparative studies between CBD and ampicillin were conducted against S. typhimurium and S. newington to determine comparative efficacy. Furthermore, we observed potential resistance development of our Salmonella spp. against CBD treatment.